(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the models of modernization of social development, their theoretical foundations, and their interrelation with Uzbekistan’s path of progress. The advantages and disadvantages of modernization, its contemporary relevance, practical challenges, and recommendations for overcoming them are discussed. The article highlights Uzbekistan’s modernization path, which is based on the harmony of national values and advanced experiences.